A Concept Study on Time-Gated Raman Spectroscopy for the Process Industry - Fritsch, T.; Tebrugge, J.; Forster, J.; Wacker, P.; Ruger, J.; Schie, I.; Weber, K.; Popp, J.; Ohrem, J.; Ostertag, E.; Boldrini, B.; Rebner, K.; et al. (2021 Conference on Lasers and Electro-Optics, CLEO 2021 - Proceedings, 2021)
A time-gated Raman spectrometer designed to meet the requirements of a hygienic industrial process analyzer is presented. It is shown that fluorescence effects can be discriminated effectively to reveal the superimposed Raman spectrum.
CRIS-Team Scopus Importer:2023-04-20